Hyphae, resignificar el inquilinato (2020)
In cities like Bogota, where different factors have developed a population fast growth, the need to bring housing is a must. However, there are some people that their only way of living is staying in the ?inquilinatos o paga diarios?, more cases do not have enough standards of living. Now, imagine a place where this population group has access to beds, restrooms, and bathrooms. A place design for changing needs. A place where it can develop and grow their community. A place that can call home.